The Potential and Limitations of Twitter Activism: Mapping the 2011 Libyan Uprising - Simon Lindgren (tripleC: Communication, Capitalism & Critique)
This article aims to shed more light on the potentials and limitations of social media as a tool for activists. It does this by focusing on the use of one particular social media platform —  Twitter — during one specific period of a certain uprising: the first 24 hours of protests in Libya during the Arab Spring in 2011. Even though this study is thus limited, it represents an important step in the direction of analyzing what actually happens when social media is put to use in relation to concrete events. The identified social network patterns, as well as the content of the posts, resonate with what Enzensberger (1970) calls “emancipatory use of media”: The architecture is decentralized, network connections are distributed, and mobilization and self-organization is going on. It must be realized however, that seeds of such emancipatory use does not necessarily preclude “repressive use of media”.